Implementasi Rencana Strategis Sekolah dalam Meningkatkan Mutu Pendidikan di Sekolah - Sherwina Ranisa; Ahmad Suriansyah; Ratna Purwanti (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to describe the implementation of the strategic plan in improving the quality of education at SMPN 3 Banjarmasin. The school’s strategic plan serves as a medium- to long-term planning document that functions as a guideline for designing priority programs to achieve the school’s vision, mission, and educational goals. A descriptive qualitative method was used, with data collected through in-depth interviews, observation, and documentation. The findings reveal that the strategic plan is implemented through a collaborative formulation of the school’s vision and mission, the development of specific goals focused on improving instructional quality and character education, and the application of participatory strategies supported by ongoing evaluation. Internal factors such as a collaborative work culture and strong leadership from the school principal have positively contributed to the success of the strategy, although challenges remain regarding limited human resources. External factors, including government policies and technological developments, also influence the adaptation of teaching strategies. The positive impacts of this implementation are reflected in improved teaching quality, increased community enthusiasm, and growing public trust in the school. These findings highlight the importance of an integrated strategic plan and active involvement from all stakeholders to ensure the sustainability of education quality.